(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Changes in the temperature of external ocular surface in patients with absolute neovascular glaucoma (including the changes after transscleral contact cyclophotocoagulation with scleral compression (TCCSC)) are still to be investigated. Purpose: To use infrared thermography (1) to investigate thermal patterns and to estimate the temperature of the external ocular surface in healthy individuals and (2) to compare these characteristics in the glaucomatous eyes versus intact fellow eyes of patients with absolute glaucoma undergoing treatment with 1064-nm TCCSC. Materials and Methods: Twenty healthy volunteers (40 eyes) and 45 patients (90 eyes) with absolute glaucoma were under observation. All 130 eyes underwent visual acuity assessment, anterior eye photography, and infrared thermography of the external corneal surface. Each patient underwent three sessions of 1 064-nm TCCSC. Results: In healthy subjects, mean external ocular surface temperature was 34.5 ± 0.7°C. For patients with absolute glaucoma, external corneal surface temperature at baseline was higher in intact fellow eyes than in glaucomatous eyes (34.3 ± 0.9°C versus 33.1 ± 0.8°С, P = 0.0008). In addition, increases in the temperature of external ocular surface were observed in the course of decrease in IOP after 1 064-nm TCCSC. Conclusion: In patients with absolute glaucoma, infrared thermography found a marked thermal pattern asymmety between glaucomatous eyes and intact fellow eyes. In addition, increases in the temperature of external ocular surface in the course of decrease in IOP after 1064-nm TCCSC may be apparently attributed to improved ocular blood flow and inflammatory response of the ciliary body to laser photocoagulation.